2022
DOI: 10.1111/nph.18121
|View full text |Cite
|
Sign up to set email alerts
|

Importation of chloroplast proteins under heat stress is facilitated by their SUMO conjugations

Abstract: Chloroplasts are hypersensitive to heat stress (HS). SUMOylation, a critical posttranslational modification, is conservatively involved in HS responses. However, the functional connection between SUMOylation and chloroplasts under HS remains to be studied.The bioinformatics, biochemistry, and cell biology analyses were used to detect the SUMOylation statuses of Arabidopsis nuclear-encoded chloroplast proteins and the effect of SUMOylation on subcellular localization of these proteins under HS. PSBR, a subunit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The process of ubiquitination plays a key role in eliminating denatured proteins and thus improves plants thermotolerance (6,12). Chloroplasts are photosynthetic organelles that also contribute to heat-stress responses (8,10,13,14). Chloroplast proteins damaged by stress need to be rapidly degraded through chloroplastic hydrolases or extraplastidic pathways (26S-proteasome and autophagy), which are well described (15)(16)(17).…”
mentioning
confidence: 99%
“…The process of ubiquitination plays a key role in eliminating denatured proteins and thus improves plants thermotolerance (6,12). Chloroplasts are photosynthetic organelles that also contribute to heat-stress responses (8,10,13,14). Chloroplast proteins damaged by stress need to be rapidly degraded through chloroplastic hydrolases or extraplastidic pathways (26S-proteasome and autophagy), which are well described (15)(16)(17).…”
mentioning
confidence: 99%
“…Moreover, a recent study indicated that the SUMO modification of various chloroproteins is essential for their precise chloroplast localization under heat stress. At least the Toc33-containing TOC complex is involved in the import of SUMOylated preproteins ( Zheng et al., 2022 ), further indicating that import regulation makes a large contribution to the shifting and rebalancing of chloroplast proteostasis in response to environmental stimuli.…”
Section: Import Of Nucleus-encoded Chloroplast Proteinsmentioning
confidence: 99%
“…SUMOylation is required for the import of nucleus-encoded chloroplast proteins in Arabidopsis under heat stress conditions (Zheng et al, 2022).…”
Section: Post-translational Regulationmentioning
confidence: 99%
“…C312) (Mishra et al, 2017), and creeping bentgrass ( Agrostis stolonifera L.) (Li et al, 2013). SUMOylation is required for the import of nucleus‐encoded chloroplast proteins in Arabidopsis under heat stress conditions (Zheng et al, 2022). SUMOylation of the TOC complex, which imports proteins into chloroplasts, was recently reported (Watson et al, 2021).…”
Section: Regulation Of the Heat Stress Responsementioning
confidence: 99%